The Influence of Service Quality, Trust, and Brand Image on Consumer Purchase Decisions of CCTM Products in Naeboruk, Viqueque District, Dili, Timor Leste - Almeida, Antonio de; Dewi, Luh Komang Candra; Karta, Luh Putuh Agustini (Jurnal Ar Ro'is Mandalika (Armada), 2025)
In a competitive business environment, understanding the factors that influence consumer decisions is crucial. Service quality, trust, and brand image are key elements that can determine purchasing decisions. This study aims to explore the influence of Service Quality, Trust, and Brand Image on the decision to purchase CCTM products in Naeboruk, Viqueque, Dili, Timor - Leste. This study uses a quantitative approach involving 100 respondents selected through purposive sampling, namely consumers who are currently and have previously purchased CCTM products. Data was collected through a questionnaire designed to measure the variables of Service Quality, Trust, and Brand Image, as well as purchasing decisions. Data analysis was conducted using multiple regression to test the influence of independent variables on purchasing decisions. The analysis results indicate that Service Quality has a positive and significant influence on consumer decisions, with a regression coefficient of 0.356 and a p-value of 0.001. Meanwhile, Trust shows a negative regression coefficient of -0.185 and a p-value of 0.062, which is not significant. Brand Image has the highest regression coefficient of 1.282 with a p-value of 0.000, indicating a significant influence on consumer decisions. The simultaneous test shows that these three variables together have a significant influence on purchasing decisions, with an F-value of 60.714 and significance of 0.000. This study concludes that Service Quality and Brand Image have a positive and significant effect on consumer purchasing decisions, while Trust is not significant. Therefore, companies need to focus on improving service quality and strengthening brand image to enhance purchasing decisions in the future.